Stabilizing and Organizing Bi3Cu4 and Bi7Cu12 Nanoclusters in Two‐Dimensional Metal–Organic Networks. (24th March 2018) - Yan, Linghao; Xia, Bowen; Zhang, Qiushi; Kuang, Guowen; Xu, Hu; Liu, Jun; Liu, Pei Nian; Lin, Nian
Abstract: Multinuclear heterometallic nanoclusters with controllable stoichiometry and structure are anticipated to possess promising catalytic, magnetic, and optical properties. Heterometallic nanoclusters with precise stoichiometry of Bi3 Cu4 and Bi7 Cu12 can be stabilized in the scaffold of two‐dimensional metal–organic networks on a Cu(111) surface through on‐surface metallosupramolecular self‐assembly processes. The atomic structures of the nanoclusters were resolved using scanning tunneling microscopy and density functional theory calculations. The nanoclusters feature highly symmetric planar hexagonal shapes and core–shell charge modulation. The clusters are arranged as triangular lattices with a periodicity that can be tuned by choosing molecules of different size. This work shows that on‐surface metallosupramolecular self‐assembly creates unique possibilities for the design and synthesis of multinuclear heterometallic nanoclusters. Abstract : Heterometall‐Nanocluster mit präzisem stöchiometrischem Verhältnis – Bi3 Cu4 und Bi7 Cu12 – können durch einen metallosupramolekularen Selbstorganisationsprozess im Gitter zweidimensionaler Metall‐organischer Netzwerke auf einer Cu(111)‐Oberfläche stabilisiert werden. Die Strukturen der Nanocluster wurden durch Rastertunnelmikroskopie aufgeklärt. Die Nanocluster haben hoch symmetrische planar‐hexagonale Formen und zeigen Kern‐Schale‐Ladungsmodulation.